Colony Collapse Disorder (CCD) in Honey Bees - Jamie Ellis (EDIS, 2007)
ENY-150, a 6-page illustrated fact sheet by Jamie Ellis, explains what is known about this new problem threatening the beekeeping industry in the U.S., its symptoms, theories about its cause, potential economic impact, what's being done, and management recommendations for beekeepers. Includes selected references. Published by the UF Department of Entomology and Nematology, May 2007.